Cr < 3 + >-doped fluoride fluorescent material with high thermal stability as well as preparation method and application of Cr < 3 + >-doped fluoride fluorescent material

Preparation of Na2MgBF7:xCr3+ in hydrothermal method in hydrofluoric acid solution solved the problem of poor thermal stability of near-infrared fluorescent materials in the prior art under high temperature environment, and achieved 85.9% emission intensity maintenance at 150°C, which is suitable for Night vision and venous imaging.

CN119193150APending Publication Date: 2024-12-27HANGZHOU DIANZI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411310670.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing near-infrared fluorescent materials exhibit poor thermal stability in high temperature environments, limiting their performance and life in practical applications.

Method used

Na2MgBF7:xCr3+ (B is Al, Ga, In) is prepared in hydrofluoric acid solution by hydrothermal method. This material can maintain a high emission intensity under high temperature environments and achieve broadband near-infrared emission.

Benefits of technology

The thermal stability of Na2MgInF7:xCr3+ at 150°C reaches 85.9%, which can be effectively used for night vision and intravenous imaging, and has high research significance and application value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119193150A_ABST
    Figure CN119193150A_ABST
Patent Text Reader

Abstract

The invention discloses a Cr < 3 + >-doped fluoride near-infrared fluorescent material as well as a preparation method and application thereof, the chemical composition formula of the material is Na2MgBF7: xCr < 3 + >, in the formula, B is one of Al, Ga or In, x is the molar percentage coefficient of doped Cr < 3 + > ions relative to Mg < 2 + > ions, 0 lt; x is less than or equal to 0.09. The fluorescent material Na2MgInF7: xCr < 3 + > disclosed by the invention can be excited by visible light and can realize broadband near-infrared emission with high thermal stability, the preparation method of the Na2MgInF7: xCr < 3 + > material disclosed by the invention is a hydrothermal method and is carried out in a hydrofluoric acid solution, and the method is simple to operate, mild in reaction condition and suitable for large-scale industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of inorganic luminescent materials, and in particular to a Cr 3+ Doped fluoride near-infrared fluorescent material and preparation method and application thereof. Background Art

[0002] Near-infrared light can be used in night vision imaging, non-destructive testing, environmental monitoring and other fields due to its advantages such as being invisible to the human eye, strong penetrability and characteristic absorption of certain molecules. Compared with the traditional halogen tungsten lamps with high energy consumption, high cost and short service life, near-infrared LEDs made of fluorescent materials have the advantages of energy saving, low cost, long life and high efficiency. Therefore, near-infrared luminescent materials have gradually attracted widespread attention in recent years.

[0003] Among the ions doped in near-infrared luminescent materials, there are 3d 3 Electronic structure of transition metal ion Cr 3+ It is easily affected by the crystal field environment and can achieve broadband emission under weak crystal fields. Compared with Yb 3+ , Er 3+ Trivalent rare earth ions, Cr 3+ As doping ions, it can make the emission peak wider and achieve coordinated emission from near-infrared region 1 to region 2. At the same time, it can be effectively excited by blue light to produce near-infrared light, which can better match commercial blue light LED chips. 3+ Doped near-infrared fluorescent materials have been developed one after another, such as Ca 3 Lu 2 Ge 3 O 12 :Cr 3+ 、CaScAlSiO 6 :Cr 3+ 、InBO 3 :Cr 3+ , Cs 2 NeaGaF 6 :Cr 3+ Although the oxide fluorescent materials have a wider half-peak width, their thermal stability is not as good as that of fluoride phosphors. This is because fluorides have a lower electron-phonon coupling effect, which is beneficial to improving the near-infrared luminescence performance and thermal stability of the materials, and can make the near-infrared LED devices prepared with fluoride fluorescent materials show more excellent performance in many practical applications. Summary of the invention

[0004] The present invention aims to provide a Cr 3+ Doped fluoride near-infrared fluorescent material and preparation method thereof, the fluorescent material Na2 MgBF 7 :xCr 3+ (B=Al, Ga, In) can be excited by visible light to achieve broadband near-infrared emission, and can be used to prepare near-infrared light source devices to achieve night vision and venous imaging functions; the present invention adopts a hydrothermal method to prepare Na 2 MgBF 7 :xCr 3+ .

[0005] A Cr with high thermal stability as claimed in any one of claims 1 to 3 3+ The preparation method of the doped fluoride near-infrared fluorescent material comprises the following steps:

[0006] Step 1: weighing raw materials sodium bifluoride, magnesium acetate tetrahydrate, B salt, and chromium nitrate nonahydrate according to a certain ratio; the B salt is any one of the chloride and oxide of B; B is any one of Al, Ga and In;

[0007] Step 2: adding sodium bifluoride, magnesium acetate tetrahydrate and salt B to the hydrofluoric acid solution, stirring for the first time, and then adding chromium nitrate nonahydrate to the solution, stirring for the second time, to obtain solution A;

[0008] Step 3: placing the solution A obtained in step 2 into a sealed container, placing the sealed container at a certain temperature for hydrothermal reaction to obtain a precipitate;

[0009] Step 4: Centrifuge, wash and dry the precipitate to obtain Na 2 MgBF 7 :xCr 3+ , x is the doped Cr 3+ Ion relative to Mg 2+ The molar percentage coefficient of the ion, 0 <x≤0.09。

[0010] Preferably, in step 1, the raw materials weighed and their molar parts are as follows: the amount of sodium bifluoride is 0.008 parts, the amount of magnesium acetate tetrahydrate is 0.002 parts, the amount of chromium nitrate nonahydrate is 2×10 -5 Servings - 1.8 x 10 -4 share;

[0011] The B salt is any one of anhydrous aluminum chloride, gallium oxide, and indium oxide; when the B salt is anhydrous aluminum chloride, the amount of the B salt is 0.002 parts; when the B salt is gallium oxide and indium oxide, the amount of the B salt is 0.001 parts.

[0012] Preferably, in step 2, the first and second stirring times are both 10-30 minutes, and the rotation speed is both 600 rpm.

[0013] Preferably, in step 3, the hydrothermal reaction specifically comprises: placing the solution A into a closed reactor, the lining of the reactor is para-polyphenol; the temperature of the hydrothermal reaction is 200° C., and the heating time is 10 hours.

[0014] Preferably, in step 4, the washing comprises: washing with deionized water for 2-3 times; the centrifugal speed is 4000-5000 rpm, and the drying method is drying in a drying oven at 60° C. for 4-6 hours.

[0015] The present invention also provides a Cr with high thermal stability 3+ Doped fluoride near-infrared fluorescent material, the chemical composition formula of the material is: Na 2 MgBF 7 :xCr 3+ , where B is one of Al, Ga or In, and x is the doped Cr 3+ Ion relative to Mg 2+ The molar percentage coefficient of the ion, 0 <x≤0.09。

[0016] Preferably, the material is an orthorhombic crystal system, and the material can be excited by visible light to emit near-infrared light, the wavelength of the visible light is 400-600 nm, and the wavelength of the excited near-infrared light is 700-1000 nm.

[0017] Preferably, the chemical composition formula of the material is Na 2 MgInF 7 :Cr 3 ; The material is an orthorhombic crystal system and the space group is Pnma.

[0018] Preferably, the unit cell parameters of the material are α=β=γ=90°.

[0019] The present invention also provides a Cr with high thermal stability 3+ The application of doped fluoride near-infrared fluorescent material is characterized by comprising the following steps: measuring the emission intensity of the material at an ambient temperature of 25°C and 150°C under a monitoring wavelength of 780nm, wherein the emission intensity of the material at 150°C reaches 85.9% of that at 25°C.

[0020] Beneficial effects of the present invention:

[0021] The materials provided by the present invention exhibit different degrees of thermal stability at 150°C, among which Na 2 MgInF 7 :xCr 3+It can be excited by visible light (blue light) to achieve broadband near-infrared emission, and its thermal stability at 150°C reaches 85.9%. Using it to prepare near-infrared light source devices can achieve night vision and venous imaging functions, which has research significance and application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the specific implementation of the present invention or the technical solutions in the prior art, the following will briefly introduce the drawings required for the specific implementation or the prior art description. Some specific embodiments of the present invention will be described in detail in an exemplary but not restrictive manner with reference to the drawings. The same reference numerals in the drawings indicate the same or similar components or parts. Those skilled in the art should understand that these drawings are not necessarily drawn to scale. In the drawings:

[0023] Figure 1 is Na in Example 1 2 MgAlF 7 :Cr 3+ XRD diffraction pattern of .

[0024] Figure 2 is Na in Example 6 2 MgGaF 7 :Cr 3+ XRD diffraction pattern of .

[0025] Figure 3 is Na in Example 11 2 MgInF 7 :Cr 3+ XRD diffraction pattern of .

[0026] Figure 4 is Na in Example 1-5 2 MgAlF 7 :Cr 3+ Room temperature emission spectrum.

[0027] Figure 5 is Na in Example 6-10 2 MgGaF 7 :Cr 3+ Room temperature emission spectrum.

[0028] Figure 6 is Na in Examples 11-15 2 MgInF 7 :Cr 3+ Room temperature emission spectrum.

[0029] Figure 7 is Na in Example 14 2 MgInF 7 :Cr 3+Room temperature excitation spectrum (monitoring wavelength is 780nm) and emission spectrum (excitation wavelength is 436nm).

[0030] Figure 8 is Na in Example 3 2 MgAlF 7 :Cr 3+ Temperature spectrum in the range of 25-250℃ (monitoring wavelength is 810nm).

[0031] Fig. 9 is Na in Example 9 2 MgGaF 7 :Cr 3+ Temperature spectrum in the range of 25-250℃ (monitoring wavelength is 810nm).

[0032] Fig.10 is Na in Example 14 2 MgInF 7 :Cr 3+ Temperature spectrum in the range of 25-250℃ (monitoring wavelength is 780nm). DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0034] Example 1

[0035] Weigh 0.4959 g of sodium bifluoride, 0.4289 g of magnesium acetate tetrahydrate, and 0.2667 g of anhydrous aluminum chloride and dissolve them in 10 ml of hydrofluoric acid, and stir at room temperature for 30 minutes. Then add 0.008 g of chromium nitrate nonahydrate to the solution and stir at room temperature for 30 minutes. Then put the resulting solution into an oven and react at 200°C for 10 hours. The resulting precipitate is washed with deionized water 3 times and finally dried in a drying oven for 4 hours. The light green powder obtained is the final product Na 2 MgAlF 7 :Cr 3+ .

[0036] The XRD diffraction pattern of this phosphor is as follows Figure 1 As shown, the diffraction peaks of the sample are consistent with the matrix Na 2 MgAlF 7 The standard card is completely consistent, and no diffraction peaks of other impurity phases are observed, which indicates that the synthesized sample has high purity and is an orthorhombic crystal system.

[0037] Example 2

[0038] Weigh 0.4959 g of sodium bifluoride, 0.4289 g of magnesium acetate tetrahydrate, and 0.2667 g of anhydrous aluminum chloride and dissolve them in 10 ml of hydrofluoric acid, and stir at room temperature for 30 minutes. Then add 0.024 g of chromium nitrate nonahydrate to the solution and stir at room temperature for 30 minutes. Then put the resulting solution into an oven and react at 200°C for 10 hours. The resulting precipitate is washed 3 times with deionized water and finally dried in a drying oven for 4 hours. The light green powder obtained is the final product Na 2 MgAlF 7 :Cr 3+ .

[0039] Example 3

[0040] Weigh 0.4959 g of sodium bifluoride, 0.4289 g of magnesium acetate tetrahydrate, and 0.2667 g of anhydrous aluminum chloride and dissolve them in 10 ml of hydrofluoric acid, and stir at room temperature for 30 minutes. Add 0.04 g of chromium nitrate nonahydrate to the solution and stir at room temperature for 30 minutes. Then put the resulting solution into an oven and react at 200°C for 10 hours. Wash the resulting precipitate with deionized water three times, and finally dry it in a drying oven for 4 hours. The light green powder obtained is the final product Na 2 MgAlF 7 :Cr 3+ .

[0041] Figure 8 The temperature-dependent spectrum of the phosphor of this example is shown in the range of 25-250° C. At 150° C., its emission intensity can maintain 19.7% of that at 25° C.

[0042] Example 4

[0043] Weigh 0.4959 g of sodium bifluoride, 0.4289 g of magnesium acetate tetrahydrate, and 0.2667 g of anhydrous aluminum chloride and dissolve them in 10 ml of hydrofluoric acid, and stir at room temperature for 30 minutes. Then add 0.056 g of chromium nitrate nonahydrate to the solution and stir at room temperature for 30 minutes. Then put the resulting solution into an oven and react at 200°C for 10 hours. The resulting precipitate is washed with deionized water 3 times and finally dried in a drying oven for 4 hours. The light green powder obtained is the final product Na 2 MgAlF 7 :Cr 3+ .

[0044] Example 5

[0045] Weigh 0.4959 g of sodium bifluoride, 0.4289 g of magnesium acetate tetrahydrate, and 0.2667 g of anhydrous aluminum chloride and dissolve them in 10 ml of hydrofluoric acid, and stir at room temperature for 30 minutes. Then add 0.072 g of chromium nitrate nonahydrate to the solution and stir at room temperature for 30 minutes. Then put the resulting solution into an oven and react at 200°C for 10 hours. The resulting precipitate is washed with deionized water 3 times and finally dried in a drying oven for 4 hours. The light green powder obtained is the final product Na 2 MgAlF 7 :Cr 3+ .

[0046] Figure 4 is Na in Example 1-5 2 MgAlF 7 :xCr 3+ The room temperature emission spectrum of (x=0.01-0.09) produces near-infrared emission under 450nm excitation.

[0047] Example 6

[0048] Weigh 0.4959 g of sodium bifluoride and 0.4289 g of magnesium acetate tetrahydrate, and 0.1874 g of gallium oxide and dissolve them in 10 ml of hydrofluoric acid, and stir at room temperature for 30 minutes. Then add 0.008 g of chromium nitrate nonahydrate to the solution and stir at room temperature for 30 minutes. Then put the resulting solution into an oven and react at 200°C for 10 hours. The resulting precipitate is washed with deionized water 3 times, and finally dried in a drying oven for 4 hours. The light green powder obtained is the final product Na 2 MgGaF 7 :Cr 3+ .

[0049] The XRD diffraction pattern of this phosphor is as follows Figure 2 As shown, the diffraction peaks of the sample are consistent with the matrix Na 2 MgGaF 7 The standard card is completely consistent, and no diffraction peaks of other impurity phases are observed, which indicates that the synthesized sample has high purity and an orthorhombic crystal structure.

[0050] Example 7

[0051] Weigh 0.4959 g of sodium bifluoride and 0.4289 g of magnesium acetate tetrahydrate, and 0.024 g of gallium oxide and dissolve them in 10 ml of hydrofluoric acid, and stir at room temperature for 30 minutes. Then add 0.024 g of chromium nitrate nonahydrate to the solution and stir at room temperature for 30 minutes. Then put the resulting solution into an oven and react at 200°C for 10 hours. The resulting precipitate is washed with deionized water 3 times, and finally dried in a drying oven for 4 hours. The light green powder obtained is the final product Na 2 MgGaF 7 :Cr 3+ .

[0052] Example 8

[0053] Weigh 0.4959 g of sodium bifluoride and 0.4289 g of magnesium acetate tetrahydrate, and 0.1874 g of gallium oxide and dissolve them in 10 ml of hydrofluoric acid, and stir at room temperature for 30 minutes. Then add 0.04 g of chromium nitrate nonahydrate to the solution and stir at room temperature for 30 minutes. Then put the resulting solution into an oven and react at 200°C for 10 hours. The resulting precipitate is washed with deionized water 3 times, and finally dried in a drying oven for 4 hours. The light green powder obtained is the final product Na 2 MgGaF 7 :Cr 3+ .

[0054] Example 9

[0055] Weigh 0.4959 g of sodium bifluoride and 0.4289 g of magnesium acetate tetrahydrate, and 0.1874 g of gallium oxide and dissolve them in 10 ml of hydrofluoric acid, and stir at room temperature for 30 minutes. Then add 0.056 g of chromium nitrate nonahydrate to the solution and stir at room temperature for 30 minutes. Then put the resulting solution into an oven and react at 200°C for 10 hours. The resulting precipitate is washed with deionized water 3 times, and finally dried in a drying oven for 4 hours. The light green powder obtained is the final product Na 2 MgGaF 7 :Cr 3+ .

[0056] Fig. 9 The temperature-dependent spectrum of the phosphor of this example is shown in the range of 25-250° C. At 150° C., its emission intensity can maintain 27.9% of that at 25° C.

[0057] Example 10

[0058] Weigh 0.4959 g of sodium bifluoride and 0.4289 g of magnesium acetate tetrahydrate, and 0.1874 g of gallium oxide and dissolve them in 10 ml of hydrofluoric acid, and stir at room temperature for 30 minutes. Then add 0.072 g of chromium nitrate nonahydrate to the solution and stir at room temperature for 30 minutes. Then put the resulting solution into an oven and react at 200°C for 10 hours. The resulting precipitate is washed with deionized water 3 times, and finally dried in a drying oven for 4 hours. The light green powder obtained is the final product Na 2 MgGaF 7 :Cr 3+ .

[0059] Figure 5 is Na in Example 6-10 2 MgGaF 7 :xCr 3+ The room temperature emission spectrum of (x=0.01-0.09) produces near-infrared emission under 450nm excitation.

[0060] Embodiment 11

[0061] Weigh 1.2398 g of sodium bifluoride, 0.2573 g of magnesium acetate tetrahydrate, and 0.27764 g of indium oxide and dissolve them in 10 ml of hydrofluoric acid, and stir at room temperature for 30 minutes. Add 0.008 g of chromium nitrate nonahydrate to the solution and stir at room temperature for 30 minutes. Then put the resulting solution into an oven and react at 200°C for 10 hours. Wash the resulting precipitate with deionized water three times, and finally dry it in a drying oven for 4 hours. The light green powder obtained is the final product Na 2 MgInF 7 :Cr 3+ .

[0062] The XRD diffraction pattern of this phosphor is as follows Figure 3 As shown, the diffraction peaks of the sample are consistent with the matrix Na 2 MgInF 7 The standard card is completely consistent, and no diffraction peaks of other impurity phases are observed, which indicates that the synthesized sample has high purity and an orthorhombic crystal structure.

[0063] Example 12

[0064] Weigh 1.2398 g of sodium bifluoride, 0.2573 g of magnesium acetate tetrahydrate, and 0.27764 g of indium oxide and dissolve them in 10 ml of hydrofluoric acid, and stir at room temperature for 30 minutes. Then add 0.024 g of chromium nitrate nonahydrate to the solution and stir at room temperature for 30 minutes. Then put the resulting solution into an oven and react at 200°C for 10 hours. The resulting precipitate is washed 3 times with deionized water and finally dried in a drying oven for 4 hours. The light green powder obtained is the final product Na 2 MgInF 7 :Cr 3+ .

[0065] Embodiment 13

[0066] Weigh 1.2398 g of sodium bifluoride, 0.2573 g of magnesium acetate tetrahydrate, and 0.27764 g of indium oxide and dissolve them in 10 ml of hydrofluoric acid, and stir at room temperature for 30 minutes. Add 0.04 g of chromium nitrate nonahydrate to the solution and stir at room temperature for 30 minutes. Then put the resulting solution into an oven and react at 200°C for 10 hours. Wash the resulting precipitate with deionized water three times, and finally dry it in a drying oven for 4 hours. The resulting light green powder is the final product Na 2 MgInF 7 :Cr 3+ .

[0067] Embodiment 14

[0068] Weigh 1.2398 g of sodium bifluoride, 0.2573 g of magnesium acetate tetrahydrate, and 0.27764 g of indium oxide and dissolve them in 10 ml of hydrofluoric acid, and stir at room temperature for 30 minutes. Add 0.056 g of chromium nitrate nonahydrate to the solution and stir at room temperature for 30 minutes. Then put the resulting solution into an oven and react at 200°C for 10 hours. Wash the resulting precipitate with deionized water three times, and finally dry it in a drying oven for 4 hours. The resulting light green powder is the final product Na 2 MgInF 7 :Cr 3+ .

[0069] Figure 7 The room temperature excitation spectrum (monitoring wavelength is 780nm) and emission spectrum (excitation wavelength is 426nm) of the phosphor of this example are shown. The embodiment of the present invention has strong broadband excitation in the blue light region (400-500nm) and the red light region (600-700nm), which can be well matched with the blue light chip. Under 426nm excitation, it has broadband near-infrared emission with a wavelength from 650-950nm, and the emission peak is at 780nm, and the half-peak width is 129nm.

[0070] Fig.10 The temperature spectrum of the phosphor of this example is shown in the range of 25-250° C. At 150° C., its emission intensity can maintain 85.9% of that at 25° C., indicating that the phosphor has high thermal stability.

[0071] Embodiment 15

[0072] Weigh 1.2398 g of sodium bifluoride, 0.2573 g of magnesium acetate tetrahydrate, and 0.27764 g of indium oxide and dissolve them in 10 ml of hydrofluoric acid, and stir at room temperature for 30 minutes. Add 0.072 g of chromium nitrate nonahydrate to the solution and stir at room temperature for 30 minutes. Then put the resulting solution into an oven and react at 200°C for 10 hours. Wash the resulting precipitate with deionized water three times, and finally dry it in a drying oven for 4 hours. The resulting light green powder is the final product Na 2 MgInF 7 :Cr 3+ .

[0073] Figure 6 is Na in Examples 11-15 2 MgInF 7 :xCr 3+ The room temperature emission spectrum of (x=0.01-0.09) produces near-infrared emission under 450nm excitation.

[0074] Table 1 is a comparison of the crystal structure parameters and thermal stability of the phosphors of Example 3, Example 9, and Example 14.

[0075] Table 1

[0076]

[0077] As shown in Table 1, at 150°C, the Na synthesized in Example 14 2 MgInF 7 :Cr 3+ It can maintain 85.9% at 25°C, compared with Na in Example 3 2 MgAlF 7 :Cr 3+ and Na synthesized in Example 9 2 MgGaF 7 :Cr 3+ Has higher thermal stability.

[0078] The above descriptions are only some specific implementation methods of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by any person familiar with the art within the technical scope disclosed in the present invention should be covered within the protection scope of the present invention.

Claims

1. A Cr with high thermal stability 3+ Doped fluoride near-infrared fluorescent material, characterized in that: The chemical composition formula of the material is: Na2MgBF7:xCr 3+ , where B is one of Al, Ga or In, and x is the doped Cr 3+ Ion relative to Mg 2+ The molar percentage coefficient of the ion, 0 <x≤0.09。 2. A Cr with high thermal stability as claimed in claim 1 3+ Doped fluoride near-infrared fluorescent material, characterized in that: The material is an orthorhombic crystal system and can be excited by visible light to emit near-infrared light. The wavelength of the visible light is between 400 and 600 nm, and the wavelength of the excited near-infrared light is between 700 and 1000 nm.

3. A Cr with high thermal stability as claimed in claim 1 3+ Doped fluoride near-infrared fluorescent material, characterized in that: The chemical composition formula of the material is Na2MgInF7:Cr 3 ; The material is an orthorhombic crystal system and the space group is Pnma.

4. A Cr with high thermal stability as claimed in claim 3 3+ Doped fluoride near-infrared fluorescent material, characterized in that: Unit cell parameters of the material α=β=γ=90°.

5. A Cr with high thermal stability as claimed in claim 4 3+ Application of doped fluoride near-infrared fluorescent material, characterized in that, The following steps are involved: Under the condition of a monitoring wavelength of 780 nm, the emission intensity of the material is measured at ambient temperatures of 25° C. and 150° C. When the material is at 150° C., the emission intensity of the material reaches 85.9% of that at 25° C.

6. A Cr with high thermal stability as claimed in any one of claims 1 to 3 3+ The method for preparing a doped fluoride near-infrared fluorescent material is characterized by: The following steps are involved: Step 1: weighing raw materials sodium bifluoride, magnesium acetate tetrahydrate, B salt, and chromium nitrate nonahydrate according to a certain ratio; the B salt is any one of the chloride and oxide of B; B is any one of Al, Ga and In; Step 2: adding sodium bifluoride, magnesium acetate tetrahydrate and salt B to the hydrofluoric acid solution, stirring for the first time, and then adding chromium nitrate nonahydrate to the solution, stirring for the second time, to obtain solution A; Step 3: placing the solution A obtained in step 2 into a sealed container, placing the sealed container at a certain temperature for hydrothermal reaction to obtain a precipitate; Step 4: Centrifuge, wash and dry the precipitate to obtain Na2MgBF7:xCr 3+ , x is the doped Cr 3+ Ion relative to Mg 2 + The molar percentage coefficient of the ion, 0 <x≤0.09。 7. A Cr with high thermal stability as claimed in claim 6 3+ The method for preparing a doped fluoride near-infrared fluorescent material is characterized by: In step 1, the raw materials weighed and their molar parts are as follows: the amount of sodium bifluoride is 0.008 parts, the amount of magnesium acetate tetrahydrate is 0.002 parts, the amount of chromium nitrate nonahydrate is 2×10 -5 Servings~1.8×10 -4 share; The B salt is any one of anhydrous aluminum chloride, gallium oxide, and indium oxide; when the B salt is anhydrous aluminum chloride, the amount of the B salt is 0.002 parts; when the B salt is gallium oxide and indium oxide, the amount of the B salt is 0.001 parts.

8. A Cr with high thermal stability as claimed in claim 7 3+ The method for preparing a doped fluoride near-infrared fluorescent material is characterized by: In step 2, the first and second stirring times are both 10-30 minutes, and the rotation speed is both 600 rpm.

9. A Cr with high thermal stability as claimed in claim 7 3+ The method for preparing a doped fluoride near-infrared fluorescent material is characterized by: In step 3, the hydrothermal reaction specifically includes: placing the solution A into a closed reactor, the inner lining of the reactor is para-polyphenol; the temperature of the hydrothermal reaction is 200° C., and the heating time is 10 hours.

10. A Cr with high thermal stability as claimed in claim 7 3+ The method for preparing a doped fluoride near-infrared fluorescent material is characterized by: In step 4, the washing includes: washing with deionized water for 2 to 3 times; the centrifugal speed is 4000 to 5000 rpm, and the drying method is drying in a drying oven at 60° C. for 4 to 6 hours.